Histo-anatomical features of garden lupin (lupinus polyphyllus lindl.) - Popoviciu, Dan Răzvan; Panaitescu , Liliana; Jeliu, Nicoleta-Veronica (Bangladesh Journal of Botany, 2024)
Lupinus polyphyllus Lindl. (garden lupin, large-leaved lupin) is a perennial herbaceous legume, used for ornamental purposes, for improving soil quality, as forage or in human food products. However, little is known about anatomical features this species’Lupin vegetative organs (roots, petioles, leaf blades) were collected, cross sectioned and analyzed by bright-field microscopy. Lupin roots showed primary and incipient secondary structures, with a cortex featuring large-sized cells with rich cellular content and granular solid inclusions. Leaf petioles had rare peltate hairs and large sub-stomatal lacunes, a large medullary lacune and rich parenchyma. Leaf blades had typical bifacial structure, with three-layered palisade tissue and less proeminent midrib, with a collateral bundle, protected by small caps of collenchyma. Bangladesh J. Bot. 53(3): 423-428, 2024 (September)